A comprehensive process for solving the problem of coarse grain ring of 6082 aluminum alloy extruded bar

By optimizing the composition and processing technology of 6082 aluminum alloy, especially the addition of La and Ce rare earth elements and the improvement of the mold runner structure, the problem of extruded rod coarse crystal ring is solved, the fine crystal structure and high mechanical properties of the material are achieved, and the automotive lightweight needs are met.

CN117965965BActive Publication Date: 2025-03-28ALNAN ALUMINIUM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311761339.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2025-03-28
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

The 6082 aluminum alloy extruded rod is prone to coarse crystal rings, resulting in cracks and performance reduction during forging, making it difficult to meet the lightweight needs of automobiles.

Method used

By optimizing the alloy composition, especially adding La and Ce rare earth elements, improving the flow structure of the extrusion mold, and using comprehensive measures such as double-stage homogenization and aluminum-titanium boron wire addition, the temperature during the homogenization and extrusion process is controlled to ensure the fine crystal structure of the ingot.

Benefits of technology

It effectively eliminates the coarse crystal ring of the 6082 aluminum alloy extruded rod, improves the mechanical properties and fatigue resistance of the material, and meets the needs of lightweight in automobiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117965965B_ABST
    Figure CN117965965B_ABST
Patent Text Reader

Abstract

A comprehensive process method for solving the coarse crystal ring of 6082 aluminum alloy extruded bar includes composition design, feeding, aluminum titanium boron wire addition, degassing and slag removal, casting, soaking, sawing car skin, extrusion, pre-stretching and solid solution, and obtains the finished 6082 aluminum alloy extruded bar forging blank. The present invention achieves the effect of eliminating the coarse crystal ring of 6082 aluminum alloy extruded bar by optimizing alloy composition design, improving the extrusion die flow channel, and controlling the temperature during soaking and extrusion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material processing, in particular to a comprehensive process method for solving the problem of coarse grain rings in 6082 aluminum alloy extruded bars. Background Art

[0002] The coarse grain ring is a ring-shaped coarse grain area formed on the periphery of the cross section of an aluminum alloy extruded product. It is a kind of structural defect of the extruded product. The grain size in the coarse grain ring can exceed 10 to 100 times the original grain size. The fatigue resistance and mechanical properties of the metal in the coarse grain area are reduced. Forging materials with this defect often produce cracks in the coarse grain area. The reason for the coarse grain is recrystallization. During forward extrusion, the strong friction between the surface of the ingot and the extrusion cylinder makes the deformation degree of the outer metal dozens of times higher than that of the central area. At the same time, the outer metal is subjected to greater shear deformation, and the grains are greatly broken, which increases the internal energy and reduces the recrystallization temperature.

[0003] 6082 aluminum alloy is a high-strength alloy type in the 6 series. It has good formability, easy welding and corrosion resistance. It is often used in the fields of transportation industry and building structure engineering. Especially with the development of new energy vehicles, automobile lightweighting has gradually become a mainstream trend. More and more passenger car suspension and steering system forgings use 6082 aluminum alloy materials. According to statistics, every 10% weight reduction of the car can reduce 6-8% of fuel consumption and exhaust emissions, 8% of 0-60km / h acceleration time and 5% of braking distance. Passenger car suspension and steering systems use 6082 aluminum alloy forgings to replace steel materials, which can achieve a weight reduction of 50-100kg, thereby meeting the requirements of automobile lightweighting. However, 6082 aluminum alloy extruded bars are also an alloy type where coarse grain rings are more likely to occur. Coarse grain rings will cause cracking and other conditions in the subsequent forging process of passenger car suspension and steering system forgings. In order to eliminate the coarse grain rings of 6082 extruded products, engineering and technical personnel have adopted a variety of methods to improve them. The existing literature on improving the coarse grain rings of aluminum alloys is retrieved as follows:

[0004] 1. A preparation method of a 6-series high-strength fine-grained aluminum alloy bar for forging automotive control arms; Application number: 202110530321.2; Abstract: An alloy of a 6-series high-strength fine-grained aluminum alloy bar for forging automotive control arms, the proportion of which is as follows: Si0.7-1.1%, Fe<0.3%, Cu0.3-0.8%, Mn0.4-0.8%, Mg0.7-1.1%, Cr 0.05-0.25%, Zn <0.2%, Zr 0.05-0.15%, and the balance AL. The main strengthening phase of this alloy is Mg2Si, and the added Cu also has a significant strengthening effect on the aluminum alloy. The mechanical strength of the alloy is improved by strictly controlling the strengthening effect of Si, Mg and Cu elements in the alloy; the addition of Cr and Zr elements curbs the tendency of grain enlargement of the material during heat treatment, reduces the generation of coarse grain rings in the material, and further improves the strength of the bar. A special structural die is used in the extrusion process to reduce the generation of coarse grain rings in the extrusion process. The mechanical properties of the final material can reach a tensile strength ≥410Mpa.

[0005] 2. A method for preparing a die forging of an Al-Mg-Si aluminum alloy with suppressed coarse-grained structure; 202110683804.6; A method for preparing a die forging of an Al-Mg-Si aluminum alloy with suppressed coarse-grained structure, the aluminum alloy comprising the following components by mass content: Mg 0.4%-1.5%, Si 0.3%-1.5%, Cu 0.01%-0.7%, Fe 0.01%-0.3%, Mn 0.01%-1.0%, Zr 0.001%-0.25%, Cr 0.01%-0.5%, Sc 0.001%-0.25%, V0.01%-0.1%, Ti 0.01%-0.25% and other transition elements, the preparation method is: melt purification treatment, near forging multi-root hot top casting, multi-stage speed control homogenization, room temperature or high temperature die forging, two-stage solid solution and aging treatment. The prepared die forgings have no coarse grains or coarse grain structure characteristics, excellent fatigue resistance and anodizing properties, and can be used to prepare aluminum alloy structural parts for vehicle traffic and transportation tools.

[0006] Although existing literature also mentions that the 6 series aluminum alloys achieve the effect of eliminating coarse grains, refining grains, and improving the metal properties of aluminum alloys by adding rare earth elements such as Zr and V, as well as multi-stage homogenization, whether other processes and methods can be used to achieve the same or even better stability effect than the original technology is a question that technical personnel in this field need to continue to explore. Summary of the invention

[0007] The purpose of the present invention is to provide a comprehensive process method for solving the coarse grain ring of 6082 aluminum alloy extruded bar, by optimizing alloy composition, improving extrusion die flow channel, and controlling the temperature during heat absorption and extrusion, so as to achieve the effect of eliminating the coarse grain ring of 6082 aluminum alloy extruded bar.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] 1. A comprehensive process for solving the problem of coarse grain ring of 6082 aluminum alloy extruded bar, characterized by comprising the following steps:

[0010] (1) Composition design: alloy element weight percentage Si: 0.9-1.2%, Fe: 0.1-0.3%, Cu: 0.01-0.03%, Mn: 0.40-0.70%, Mg: 0.7-1.0%, Cr: 0.13-0.20%, Zn: ≤0.1%, Ti: 0.02-0.05%, La: 0.005-0.02%, Ce: 0.005-0.02%; the balance is Al;

[0011] Compared with the national standard, the content of Fe, Cu, Cr and Ti is specially controlled. The content of Fe, a small amount of iron has no adverse effect on the mechanical properties of the alloy, and can form a high-temperature phase in the subsequent process to increase the recrystallization value (increase the recrystallization temperature), thereby eliminating coarse grains to a certain extent. Controlling a certain Cu content, a small amount of Cu can be dissolved in the matrix, which plays a role in strengthening the alloy during heat treatment, and at the same time eliminates the anisotropy caused by Mn (Mn itself has a grain boundary adsorption phenomenon, which inevitably causes intracrystalline segregation. The recrystallization temperature is high in places with high Mn, and the recrystallization temperature is low in places with low Mn. Therefore, coarse grains are easily produced in areas with low Mn). Adding a certain amount of Cu can eliminate this inhomogeneity to a certain extent, thereby inhibiting the generation of coarse grains.

[0012] The addition of La and Ce rare earth elements has a strong affinity with hydrogen and plays a role in absorbing hydrogen and impurities in the solution (forming multi-component compounds such as RES and REPb) to purify the solution. At the same time, the addition of these two rare earth elements reduces the surface tension of the grain boundary during the solidification of the melt, increases the growth rate of the crystal nucleus, and forms a surface active film between the grain and the melt, which can inhibit the growth of the grain to a certain extent and play a role in refining the crystal. La and Ce belong to the same type of elements. Adding them together can complement each other compared to adding them alone, achieving 1+1>2.

[0013] Feeding: Feeding is done in batches. First, Si and aluminum ingots are fed. Then, Mn, Cr, and Cu are fed into the melted alloy to ensure that the gold melts quickly and evenly. Then, Fe, Mg, La, and Ce alloys are added into the static furnace.

[0014] The materials are fed in batches. Si and aluminum ingots are fed first. Then, the intermediate alloy containing Mn, Cr and Cu is fed into the molten alloy to ensure that the intermediate alloy melts quickly and evenly. Finally, Fe, Mg, La and Ce alloys are added into the static furnace to prevent Fe from sinking to the bottom and causing unevenness, and to ensure that Mg reduces burning loss. La and Ce are used to ensure that the time to casting is controlled within the optimal failure time as much as possible.

[0015] (3) Addition of aluminum-titanium-boron wire: The feed speed is controlled at 800-1200 mm / min; the imported aviation-grade titanium-boron wire AlTi5B1-φ11 from KBM is used for online addition. If the feed speed is too slow, the refinement effect cannot be achieved; if the feed speed is too fast, the melting is uneven. Only when the refinement effect is good can the ingot be controlled within the first-level grain size.

[0016] (4) Degassing and slag removal: The ratio of chlorine-argon mixed gas is 5%~40%, the gas flow rate is 5~15m³ / h, and the four-stage degassing is carried out: the first stage of degassing and slag removal is carried out in the static furnace, the second stage of degassing and slag removal is carried out online in the flow trough with chlorine-argon gas, the third stage of degassing and slag removal is carried out online in the flow trough with argon gas, and the fourth stage of filtering gas and slag before casting; the four-stage degassing is to ensure the density and uniformity of the ingot.

[0017] (5) Casting: Hot top semi-continuous casting is adopted, the casting temperature is 690-720℃, the water flow rate is 120-180m³ / h; the cooling water flow rate is 120-180m³ / h, to ensure rapid cooling under the premise of forming, make the ingot grains finer, and inhibit the growth of the second phase;

[0018] (6) Heat absorbing: two-stage heat absorbing, first stage: 400-420℃ / 5-10h; second stage: 545-565℃ / 10-30h; cooling rate after heat absorbing: 300-500℃ / h; cooling rate after heat absorbing: 300-500℃ / h; the first stage temperature is conducive to the spheroidization and dissolution of the iron-manganese-chromium refractory phase in the cast state, and is more conducive to the precipitation of the precipitate phase that inhibits the recrystallization size. The second stage is to thoroughly dissolve the cast phase in the 6 series alloy evenly, and the rapid cooling of the cooling water can prevent the precipitate phase from precipitating and growing in time during the cooling process, and obtain the precipitate phase size that inhibits recrystallization.

[0019] (7) Sawing the car body: After equalization, cut off the head and tail ingots above 200 mm, and carve off the surface segregation layer above 10 mm; ensure the uniformity of the composition of the cross section of the extruded ingot, and prevent the stains on the surface from being brought into the extrusion barrel during extrusion.

[0020] (8) Extrusion: mold temperature control: 440-490℃, ingot preheating temperature: 490-540℃, ingot gradient heating, extrusion barrel temperature control: 430-450℃, extrusion speed control: 2-3m / min, the temperature of the extruded bar at the front beam outlet is controlled at 520-530℃;

[0021] The key points of extrusion are: isothermal and constant speed of the extruded round bar at the extrusion outlet, gradient heating of the ingot, that is, heating the ingot at different temperatures in the length direction, so as to achieve the effect of high temperature at the head and low temperature at the tail of the ingot, and matching the extrusion speed, mold temperature and extrusion barrel temperature to achieve isothermal and constant speed of the extruded round bar at the extrusion outlet. The quenching tank at the front beam outlet should be as short as possible to ensure the quenching temperature and cooling speed. The extrusion barrel should be cleaned up. Any metal residue will affect the deformation of the extruded rod during the extrusion process, resulting in the difference in energy storage and the appearance of coarse grains.

[0022] (9) Pre-stretching: The stretching rate of the tension stretching machine is 0.3%-0.5%; it can release the extrusion deformation energy to a certain extent and reduce the subsequent coarse grains. If the deformation is small, the effect cannot be achieved, and if the deformation is large, the distortion will increase instead.

[0023] (10) Solution treatment: Heat to 500-550℃ in a roller-bottom quenching furnace, keep warm for 1-2h, then spray water to cool to room temperature; roller-bottom solution treatment can greatly ensure uniform heating of the bar. The waiting time during quenching is almost negligible, which is an instantaneous transfer. The solution treatment effect provides sufficient atomic vacancies for the subsequent dispersed and uniform precipitation phase during aging. At the same time, the second phase obtained after extrusion of the homogenized ingot in the previous process plays a role in inhibiting recrystallization to a certain extent during the solution treatment process.

[0024] After solution treatment, the bar is straightened, stretched, aged and sawn again to finally obtain the finished 6082 aluminum alloy extruded bar forging billet.

[0025] In the step (8), the mold adopts a double-conical necking guide pad, the feed end is a conical necking with a taper of 30-60°, and the discharge end is a micro-conical expansion with a taper of 3-5°.

[0026] When extruding traditional aluminum alloy bars, there is generally no guide structure, and a large metal flow dead zone is generated between the extrusion barrel and the die end face. The metal generates turbulence in the dead zone, causing the grains to recrystallize here. The feed end of the present invention is a conical necking port to guide the metal fed into the extrusion barrel, so that the metal flowing into the die flows more smoothly. The diameter of the guide inlet is closer to the size of the ingot, the extrusion dead zone is smaller, and the probability of turbulence and turbulence of the metal is lower, thereby reducing the mutual friction between the metals and greatly reducing the probability of coarse grains.

[0027] The discharge end is a slightly tapered expansion to form a shrinkage in the middle of the guide pad. The metal at the shrinkage has a positioning effect. During the process of cutting the excess after an ingot is extruded, the tail of the extruded bar will not be pulled out of the die due to the pulling effect of the excess scissors. This ensures that the tail of the previous extruded bar is connected to the tail of the next bar, avoiding discontinuous extrusion of the extruded bar, resulting in abnormal traction and quenching, and ultimately leading to the extruded bar being unable to be cooled in time, causing grain growth and forming a coarse grain ring.

[0028] In the step (1), the amount of La added is 0.015%; the amount of Ce added is 0.015%-0.02%.

[0029] In the step (6), the process control of the double-stage equalization is: first stage: 420°C / 10h; second stage: 565°C / 30h; rapid cooling 500°C / h.

[0030] Advantages of the present invention:

[0031] 1. The present invention optimizes the alloy composition of the traditional 6082 aluminum alloy, and especially adds La and Ce rare earth elements, which have a strong affinity with hydrogen and play a role in absorbing hydrogen and impurities in the solution. The impurities are discharged from the melt along with the degassing filtration, thereby purifying the solution. The rare earth elements that have not formed impurity compounds exist as fine particles to become heterogeneous crystal nuclei of aluminum, thereby refining the grains; at the same time, the addition of these two rare earths reduces the surface tension of the grain boundaries during the solidification process of the melt, increases the growth rate of the crystal nuclei, and forms a surface active film between the grains and the melt, thereby inhibiting the growth of the grains to a certain extent.

[0032] 2. The present invention optimizes the process parameters of double-stage soaking. Compared with the traditional single-stage soaking process, the first stage first adopts a relatively low soaking temperature to preheat and keep the iron-manganese-chromium refractory phase in the cast state, which is more conducive to the precipitation of the precipitate phase that inhibits the recrystallization size in the second-stage soaking. At the same time, the metal can be slowly heated to the corresponding insulation temperature by graded heating, so that the intergranular precipitation zone is narrower or even absent. Finally, the second stage thoroughly dissolves the cast phase in the alloy evenly, and the rapid cooling of the cooling water can prevent the precipitation phase from precipitating and growing in the cooling process, thereby obtaining the ideal precipitation phase size that inhibits recrystallization.

[0033] 3. The present invention adopts a double-conical necking guide pad structure. The feed end is a conical necking to guide the metal fed into the extrusion barrel, so that the metal flowing into the mold flows more smoothly. The diameter of the guide inlet is closer to the size of the ingot, the extrusion dead zone is smaller, and the probability of turbulence and turbulence of the metal is lower, thereby reducing the mutual friction between the metals and greatly reducing the probability of coarse grain generation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is the as-cast structure of the 6082 ingot before soaking, which is prone to produce coarse crystal rings. In the figure, the dendrites are well-developed and the second phase is coarse, which makes it more difficult to break in the subsequent extrusion process, resulting in hereditary characteristics in the extruded rods, which is more likely to cause coarse crystals in the finished product; (Example 1)

[0035] Figure 2 This is the as-cast structure of the 6082 ingot before soaking, which is less likely to produce coarse crystal rings; it is obvious that the grains are finer and more uniform, the second phase is smaller, the impurities are less, and the structure is more uniform. The finer the original grains of the ingot, the more crystal interfaces there are, thus increasing the nucleation rate. Even if a certain degree of coarse crystals occur, the size of the coarse crystals will be smaller, thereby reducing the generation of coarse crystals during extrusion to a certain extent. (Example 3-3)

[0036] Figure 3 The as-cast structure of the 6082 ingot before soaking to further reduce the possibility of producing a coarse grain ring; (Example 4-3)

[0037] Figure 4 This is the as-cast structure of the 6082 ingot after soaking, which is prone to produce coarse crystal rings; in the figure, the soaking time is short and the second phase is not completely disconnected and melted, and the second phase is coarse. The second phase inheritance effect is obvious during extrusion, and the precipitated phase in the crystal is relatively coarse, and the coarse phase is greater than 1μm and cannot inhibit recrystallization. (Ingot after step 6 in Example 1)

[0038] Figure 5 This is the as-cast structure of the 6082 ingot after soaking, which is less likely to produce coarse crystal rings. In the figure, the soaking time is long, the second phase is obviously melted and spheroidized, the precipitation phase is smaller and more uniform, and the pinning effect on the grain boundary during recovery and crystallization is obvious, which hinders the uniform growth of recrystallized grains. (Example 2-2)

[0039] Figure 6 The as-cast structure of the 6082 ingot after soaking to eliminate the possibility of the coarse crystal ring; the best suppression of recrystallization structure in the figure is fine, the second phase is fully disconnected, and the whole is uniform. The second phase particles dispersed in the crystal play an important role in the movement of the grain boundary. The grain size is proportional to the particle radius and inversely proportional to the particle volume fraction. Therefore, the smaller the particle, the stronger the effect of hindering the growth of the grain. Through this soaking, the coarse crystal problem of the extruded rod is eliminated. (Example 2-4)

[0040] Figure 7 This is a low-magnification structural picture of Example 1; an obvious coarse crystal ring can be seen with the naked eye;

[0041] Figure 8 This is a low-magnification structural picture of Example 3-1; there is a thin coarse-grained ring layer on the outer surface;

[0042] Fig. 9 This is a low-magnification structural picture of Example 4-3; no coarse crystal ring layer is visible to the naked eye;

[0043] Fig.10 This is a low-magnification structural picture of Example 4-4; no coarse crystal ring layer is visible to the naked eye;

[0044] Fig.11 The schematic diagram of the structure of the double-cone shrinkage guide pad is adopted; Implementation Example 1

[0045] The production of 6082 aluminum alloy φ40mm extruded bars includes the following steps:

[0046] (1) Composition design: alloy element weight percentage Si: 0.95, Fe: 0.1, Cu: 0.005, Mn: 0.45, Mg: 0.8, Cr: 0.13, Zn: 0.012, Ti: 0.025, balance Al;

[0047] (2) Feeding: Feeding is done in batches. First, Si and aluminum ingots are fed. Then, Mn, Cr, and Cu are fed into the melted alloy. If the content of Mn, Cr, and Cu is relatively low, no additional addition is required. The impurities in the original metal contain Cu elements. This ensures that the intermediate alloy melts quickly and evenly. Finally, Fe and Mg alloys are added into the static furnace.

[0048] (3) Addition of aluminum titanium boron wire: feed speed controlled at 1000 mm / min;

[0049] (4) Degassing and slag removal: the ratio of chlorine-argon mixed gas is 30%, the gas flow rate is 10m³ / h, and the four-stage degassing is: the first stage of degassing and slag removal is carried out in the static furnace, the second stage of degassing and slag removal is carried out online in the flow trough with chlorine-argon gas, the third stage of degassing and slag removal is carried out online in the flow trough with argon gas, and the fourth stage of filtering gas slag before casting;

[0050] (5) Casting: Hot top semi-continuous casting, casting temperature 710℃, water flow rate 150m³ / h;

[0051] (6) Heat soaking: Normal heat soaking at 560℃ for 12h, cooling rate after heat soaking: 200-250℃ / h;

[0052] (7) Sawing the car body: After soaking, cut off the 250mm head and tail ingots, and cut off the 12mm surface segregation layer;

[0053] (8) Extrusion: mold temperature control: 480℃, ingot preheating temperature from tail to head is gradient temperature: 490℃, 500℃, 510℃, 520℃, extrusion barrel temperature control: 450℃, extrusion speed control: 2-3m / min, extruded bar outlet temperature at the front beam is controlled at 520-530℃;

[0054] (9) Pre-stretching: the stretching rate of the tension stretching machine is 0.4%;

[0055] (10) Solution treatment: Heat to 500-550°C in a roller-bottom quenching furnace, keep warm for 1-2 hours, then spray water to cool to room temperature;

[0056] In the step (8), a common non-guiding rod extrusion die is used.

[0057] Example 1-1

[0058] The difference from Example 1 is that in step (8), the mold adopts a double-conical necking guide pad, the feed end is a conical necking with a taper of 45°, and the discharge end is a slightly conical expansion with a taper of 4°.

[0059]

[0060] It can be seen that the use of double-cone shrinkage guide pads can greatly reduce the occurrence of coarse grain rings and traction breakage, which has a positive effect on the production of 6082 extruded round bars.

[0061] Example 2-1 to Example 2-5

[0062] Examples 2-1 to 2-5 are based on Example 1-1, and different two-stage equalization processes are tested; different equalization processes are compared, and the second phase dissolution, metal component uniformity, and tissue precipitation are observed using an electron microscope.

[0063]

[0064] As can be seen from the table above, the optimal two-stage soaking process control is Example 2-4: first stage: 420℃ / 10h; second stage: 565℃ / 30h; rapid cooling 500℃ / h; the reason why this process further refines the grains is that the refractory phase is more appropriately preserved under the first stage soaking conditions, which is more fully prepared for subsequent precipitation. The temperature of the second stage is increased and the extended soaking time is very beneficial to the full melting of the second phase, and the second phase of the structure is further refined. However, the effect of further extending the soaking time on the alloy structure is not much changed, and the second phase still has a certain growth trend, and the energy consumption increases when the soaking time is extended.

[0065] Example 3-1 to Example 3-5

[0066] The difference is that: on the basis of Examples 2-4, the weight percentages of La alloy elements added to the static furnace are 0%, 0.005%, 0.01%, 0.015%, 0.02% and 0.025% respectively; the Ce alloy element added is 0%. The head and tail of the extruded rod are cut off, and the qualified area is sampled for low-power observation in alkali solution, and the surface material of the extruded rod is taken from the qualified area to make a mechanical specimen for mechanical property testing.

[0067] Finally, the following table is obtained from the test of 6082 alloy extruded round bars:

[0068]

[0069] It can be seen from the above table that when La is added to 0.015% and 0.02%, the coarse grain ring of the extruded round rod is eliminated, and the mechanical properties reach the best. When the La addition exceeds 0.025%, the coarse grains are slightly re-generated. The reason is that when La is excessive, it will produce a certain micro-alloying effect with elements such as Al. Although the distribution of intermetallic compounds in the grains or grain boundaries has a certain beneficial effect on the alloy properties, it has little effect on the elimination of coarse grains or weakens it.

[0070] Example 4-1 to Example 4-5

[0071] The La alloy element was added into the static furnace at a weight percentage of 0.015%; the Ce alloy elements were added at 0.005%, 0.01%, 0.015%, 0.02% and 0.025% respectively; the head and tail of the extruded rod were cut off, and samples were taken from the qualified area for low-power observation in alkali solution, and the surface material of the extruded rod in the qualified area was made into mechanical specimens for mechanical property testing.

[0072]

[0073] It can be seen from the above table that when Ce is added to 0.02% on the basis of 0.015% by weight of La alloy element, not only the coarse grain ring of the extruded round rod is eliminated, but also the mechanical properties are further improved. When the La addition exceeds 0.025%, the coarse grains are slightly re-generated. The reason is that when the Ce and La contents exceed a certain content, the intermetallic compounds produced by this type of rare earth and Al and other elements in the alloy begin to change in shape, forming short rods and small needles distributed in the alloy structure, which has a certain splitting effect on the alloy structure and has a certain adverse effect on the coarse grains and mechanical properties.

Claims

1. A comprehensive process for solving the problem of coarse grain ring of 6082 aluminum alloy extruded bar, characterized in that: The process comprises the following steps: (1) composition design: alloy element weight percentage Si: 0.9-1.2%, Fe: 0.1-0.3%, Cu: 0.01-0.03%, Mn: 0.40-0.70%, Mg: 0.7-1.0%, Cr: 0.13-0.20%, Zn: ≤0.1%, Ti: 0.02-0.05%, La: 0.015%, Ce: 0.015%-0.02%; the balance is Al; (2) feeding: feeding in batches, first feeding Si and aluminum ingots, then feeding Mn, Cr, and Cu into the molten alloy, and finally adding Fe, Mg, and Ce in a static furnace. La, Ce alloy; (3) Aluminum titanium boron wire addition: feed speed control 800-1200mm / min; (4) Degassing and slag removal: use chlorine argon mixed gas ratio: 5%~40%, gas flow rate: 5~15m³ / h, four-stage degassing: the first stage of degassing and slag removal is carried out in the static furnace, the second stage is online degassing and slag removal with chlorine argon in the flow channel, the third stage is online degassing and slag removal with argon in the flow channel, and the fourth stage is to filter the gas slag before casting; (5) Casting: hot top semi-continuous casting is adopted, the casting temperature is 690-720℃, and the water flow rate is 120-180m³ / h; (6) Heating: two-stage heating, the first stage: 400-430℃ / 5-10h; Second stage: 545-565℃ / 10-30h; cooling rate after aeration: 300-500℃ / h; (7) Sawing car skin: after aeration, cut off the head and tail ingots above 200mm, and turn off the surface segregation layer above 10mm; (8) Extrusion: mold temperature control: 440-490℃, ingot preheating temperature: 490-540℃, ingot gradient heating, extrusion barrel temperature control: 430-450℃, extrusion speed control: 2-3m / min, the temperature of the extruded bar at the front beam outlet is controlled at 520-530℃; (9) Pre-stretching: tensile stretching machine stretching rate 0.3%-0.5%; (10) Solution treatment: heating at 500-550℃ in a roller bottom quenching furnace, keeping warm for 1-2h, and then spraying water to cool to room temperature; the bar after solution treatment is straightened, stretched, aged and sawed again, and finally a qualified sample of 6082 aluminum alloy extruded bar is obtained; In the step (8), the mold adopts a double-conical necking guide pad, the feed end is a conical necking with a taper of 30-60°, and the discharge end is a micro-conical expansion with a taper of 3-5°.

2. The comprehensive process for solving the coarse grain ring of 6082 aluminum alloy extruded bar according to claim 1 is characterized in that: In step (6), the process control of the two-stage equalization is as follows: first stage: 420°C / 10h; Second stage: 565℃ / 30h; Rapid cooling 500℃ / h.

Citation Information

Patent Citations

  • A method for preparing Al-Mg-Si aluminum alloy forgings with suppressed coarse-grained structure

    CN113245486B

  • A method for preparing 6-series high-strength fine-grained forged aluminum alloy bars for automotive control arms

    CN113265569B

  • Rare earth aluminum alloy and preparation method thereof

    CN103014443A

  • 6082 aluminum alloy extruded bar production process capable of controlling coarse grains after forging

    CN116144989A